2005
DOI: 10.1002/cbic.200500019
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Aminocoumarins: Inactivation of the Methyltransferase Gene cloP and Generation of New Clorobiocin Derivatives in a Heterologous Host

Abstract: Aminocoumarin antibiotics are highly potent inhibitors of bacterial gyrase and represent a class of antibiotics that are very suitable for the generation of new compounds by metabolic engineering. In this study, the putative methyltransferase gene cloP in the biosynthetic gene cluster of clorobiocin was inactivated. Expression of the modified gene cluster in the heterologous host Streptomyces coelicolor M512 gave three new aminocoumarin antibiotics. The structures of the new compounds were elucidated by MS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
4
16
0
Order By: Relevance
“…This showed that in compound 2 the 5-chloropyrrole-2-carboxylic acid moiety was attached to the 2''-OH group rather than to the 3''-OH group (Schemes 1 and 2). Similar 2''-acylated compounds have been found in earlier studies [13,25,26] and showed very similar NMR spectroscopic signals of H2'' and H3'' as compound 2. Therefore, the structure shown in Scheme 2 was assigned to compound 2, and this second new clorobiocin derivatives was designated as novclobiocin 125.…”
Section: Analysis Of Secondary Metabolitessupporting
confidence: 71%
“…This showed that in compound 2 the 5-chloropyrrole-2-carboxylic acid moiety was attached to the 2''-OH group rather than to the 3''-OH group (Schemes 1 and 2). Similar 2''-acylated compounds have been found in earlier studies [13,25,26] and showed very similar NMR spectroscopic signals of H2'' and H3'' as compound 2. Therefore, the structure shown in Scheme 2 was assigned to compound 2, and this second new clorobiocin derivatives was designated as novclobiocin 125.…”
Section: Analysis Of Secondary Metabolitessupporting
confidence: 71%
“…The current study completes the functional identification of the three methyltransferases contained in the clorobiocin cluster, i.e. CloP (Freitag et al, 2005), CloN6 (Westrich et al, 2003) and CloU (present study).…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, the signal for 20-H is shifted strongly downfield to 5?36 p.p.m. This shows that the acyl moiety is attached to 20-OH rather than to 30-OH, similar to observations in previous studies (Freitag et al, 2005;Galm et al, 2004). The negative mass spectra showed the same molar ion as observed for novclobiocin 122.…”
Section: Structural Elucidationsupporting
confidence: 90%
“…The fractions after separation on Sephadex LH 20 were analyzed by high-performance liquid chromatography. Fractions containing novclobiocin 103 were pooled and further purified by high-performance liquid chromatography on a Multosphere RP18-5 column (250 by 4 mm; 5-m particle size; CϩS Chromatographie Service, Düren, Germany) at a flow rate of 1 ml/min, using a linear gradient Novclobiocins 101, 103, 104, 105, 107, 112, 113, 114, 117, and 120 were produced as described previously (3)(4)(5)24). A summary of the lineage of the novclobiocins is given in Fig.…”
Section: Methodsmentioning
confidence: 99%